Harnessing Arsenic Derivatives and Natural Agents for Enhanced Glioblastoma Therapy - Bo Yuan; Hidetomo Kikuchi (Cells)
Glioblastoma (GBM) is the most common and lethal intracranial tumor in adults. Despite advances in the understanding of the molecular events responsible for disease development and progression, survival rates and mortality statistics for GBM patients have been virtually unchanged for decades and chemotherapeutic drugs used to treat GBM are limited. Arsenic derivatives, known as highly effective anticancer agents for leukemia therapy, has been demonstrated to exhibit cytocidal effects toward GBM cells by inducing cell death, cell cycle arrest, inhibition of migration/invasion, and angiogenesis. Differentiation induction of glioma stem-like cells (GSCs) and inhibition of neurosphere formation have also been attributed to the cytotoxicity of arsenic derivatives. Intriguingly, similar cytotoxic effects against GBM cells and GSCs have also been observed in natural agents such as anthocyanidins, tetrandrine, and bufadienolides. In the current review, we highlight the available data on the molecular mechanisms underlying the multifaceted anticancer activity of arsenic compounds and natural agents against cancer cells, especially focusing on GBM cells and GCSs. We also outline possible strategies for developing anticancer therapy by combining natural agents and arsenic compounds, as well as temozolomide, an alkylating agent used to treat GBM, in terms of improvement of chemotherapy sensitivity and minimization of side effects.